Peranan Pemerintah Kota dalam Meningkatkan Kesehatan di Lingkungan Kota - Ahmad Rohili (Asosiasi Ahli Administrasi Indonesia, 2020)
Many development policies, one of which is development in the health sector. The community has the right to obtain the same degree of health and is obliged to participate in health businesses run by the government. In order to obtain these, various efforts are needed to fulfill the basic needs of the Indonesian people, which are essentially fulfilled clothing, food, shelter, health and education. The role of local government in improving environmental health is outreach, coordination with related elements, approaches to community leaders. The factors that support the role of the government are informal leaders and social institutions. By carrying out the role and support of all parties, it is hoped that environmental health will be achieved for all communities.